TA'ZIR AGAINST HUMAN SELF-EXPLOITATION BEHAVIOR SILVER, ANALYSIS FROM THE PERSPECTIVE OF MAQASHID SYARI'A - Mardiyah, Daiyatul; Azizah, Noor (Program Pascasarjana UIN Sumatera Utara Medan, 2025)
Silver humans, individuals who paint their entire bodies with metallic paint and appear in public spaces to beg, have become a common sight in various major cities in Indonesia. This practice not only poses health risks due to exposure to hazardous chemicals, but also raises social and legal issues. According to Article 504 of the Criminal Code, begging in public places is a criminal offense punishable by imprisonment. However, the positive legal approach focuses more on punishment than rehabilitation. This study aims to analyze the behavior of silver human exploitation from the perspective of Islamic criminal law with a focus on ta'zir sanctions and the principles of maqashid syari'ah. The research method used is a normative approach with qualitative analysis of fiqh literature, maqashid syari'ah, and relevant laws and regulations. The results of the study found that the behavior of silver human exploitation is contrary to the five main objectives of sharia: protecting religion (hifz al-din), life (hijz al-nafs), reason (hifz al-'aql), offspring (hifz al-nasl), and property (hifz al-mal). Therefore, imposing ta'zir sanctions that are educational and rehabilitative in nature is more appropriate for creating public interest than simply imposing imprisonment as stipulated in the Criminal Code. This study emphasizes the importance of synergy between positive law and Islamic criminal law in formulating policies that protect perpetrators while maintaining public order.